2017
DOI: 10.1111/sltb.12329
|View full text |Cite
|
Sign up to set email alerts
|

Friendship, Depression, and Suicide Attempts in Adults: Exploratory Analysis of a Longitudinal Follow‐Up Study

Abstract: Social support is thought to protect against the risk of suicidal behavior in young people and late life, but less is known about the role of friendship in adults. We explored the effect of friendship on suicide attempt risk during 1-year follow-up of 132 adults presenting with major depressive episode (MDE). Items from the Social Adjustment Scale-Self-Report were used as an index of frequency and quality of recent friendship contacts. Survival methods tested associations of friendship with risk of suicide att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 50 publications
2
11
0
1
Order By: Relevance
“…Most studies of friendship have assessed its effects on mental and physical health outcomes [52,53], but not on suicidal behavior. Marver et al [21] explored the effect of friendship on suicide attempt risk during one-year follow-up of 132 adults presenting with a major depressive episode and concluded that impaired friendship predicted a greater risk of suicide attempt. The explanation is that friendship has a potentially bidirectional relationship with depression, and that its effect on suicidal behavior occurs through its relationship with depression [21].…”
Section: Plos Onementioning
confidence: 99%
“…Most studies of friendship have assessed its effects on mental and physical health outcomes [52,53], but not on suicidal behavior. Marver et al [21] explored the effect of friendship on suicide attempt risk during one-year follow-up of 132 adults presenting with a major depressive episode and concluded that impaired friendship predicted a greater risk of suicide attempt. The explanation is that friendship has a potentially bidirectional relationship with depression, and that its effect on suicidal behavior occurs through its relationship with depression [21].…”
Section: Plos Onementioning
confidence: 99%
“…Friendship is closely related to social adaptability, subjective well-being, and mental health. People with fewer friends were at a higher risk of suicide ideation, which was largely explained by self-assessed depression [ 59 ]. Teo’s research confirmed that high-quality social relationships were protective against depression [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…57 Social support comprises multiple dimensions, including the quantity and quality of support and perceived social support, and may be derived from multiple sources, including family, friends, colleagues and the community. 58 Previous studies have demonstrated that satisfactory social support can reduce the occurrence of psychological stress disorder to a certain extent, improve the ability of injured patients to handle traumatic events, and provide long-term protection in individuals through mediators, 59 while poor social support is associated with depression, 60 suicide, 61,62 anxiety disorders, schizophrenia, and bipolar disorder. 63 Our results showed that low social support is a risk factor for ASD.…”
mentioning
confidence: 99%